Política educacional, ensino fundamental e metas de desempenho : diagnóstico da Região Nordeste e propostas de ação - Melo, Gabriel Barreto de (2016)
The Índice de Desenvolvimento da Educação Básica - IDEB is one of the most relevant indicators of school performance in Brazil at the present time, and can be generated at the national, state, municipal, school networks and even in school level. That indicator is also generated considering the school phases in the early years, later years and high school. In order to improve the performance of basic education in Brazil, the Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira - INEP set individualized targets for each level of measurement. Considering the IDEB values for the final years of elementary public school, the Brazilian Northeast had several States that have not reached the targets set by INEP in 2013. In this context, this study aims to diagnose factors related to insufficient performance, and suggest actions in order to improve the educational indicators in that Brazilian region. Through quantitative methodology using data from INEP, relationships between different variables were analyzed. It was found that in States with lower average in IDEB, the presence of student delays showed up higher. It was also found that the use of lower student yields is not associated with better outcomes in proficiency measured by Prova Brasil. Based on these results, proposals have been suggested to the Government of the Northeast States to be guided in order to raise student achievements, especially in the Federal States in more troublesome situations.